Heterogeneous engineered cartilage growth results from gradients of media-supplemented active TGF-β and is ameliorated by the alternative supplementation of latent TGF-β. (January 2016) - Albro, Michael B.; Nims, Robert J.; Durney, Krista M.; Cigan, Alexander D.; Shim, Jay J.; Vunjak-Novakovic, Gordana; Hung, Clark T.; Ateshian, Gerard A.
Abstract: Transforming growth factor beta (TGF-β) has become one of the most widely utilized mediators of engineered cartilage growth. It is typically exogenously supplemented in the culture medium in its active form, with the expectation that it will readily transport into tissue constructs through passive diffusion and influence cellular biosynthesis uniformly. The results of this investigation advance three novel concepts regarding the role of TGF-β in cartilage tissue engineering that have important implications for tissue development. First, through the experimental and computational analysis of TGF-β concentration distributions, we demonstrate that, contrary to conventional expectations, media-supplemented exogenous active TGF-β exhibits a pronounced concentration gradient in tissue constructs, resulting from a combination of high-affinity binding interactions and a high cellular internalization rate. These gradients are sustained throughout the entire culture duration, leading to highly heterogeneous tissue growth; biochemical and histological measurements support that while biochemical content is enhanced up to 4-fold at the construct periphery, enhancements are entirely absent beyond 1 mm from the construct surface. Second, construct-encapsulated chondrocytes continuously secrete large amounts of endogenous TGF-β in its latent form, a portion of which undergoes cell-mediated activation and enhances biosynthesis uniformly throughout the tissue. Finally, motivated by these prior insights, we demonstrate that the alternative supplementation of additional exogenous latent TGF-β enhances biosynthesis uniformly throughout tissue constructs, leading to enhanced but homogeneous tissue growth. This novel demonstration suggests that latent TGF-β supplementation may be utilized as an important tool for the translational engineering of large cartilage constructs that will be required to repair the large osteoarthritic defects observed clinically.